1994
DOI: 10.1246/cl.1994.2307
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Bromo-ether Cyclization of Laurediols with Bromoperoxidase

Abstract: Natural (3E,6R,7R)- and (3Z,6S,7S)-laurediols were subjected to enzymatic reaction with the partially purified bromoperoxidase from the red alga, Laurencia nipponica, in the presence of H2O2 and NaBr to afford laurencin and prelaureatin, respectively. The further reaction of these products with bromoperoxidase gave rise to the bicyclic bromo-ethers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 4 publications
0
37
0
3
Order By: Relevance
“…Further reaction of deacetyllaurencin with BrPO yielded bicyclic ACGs such as laurefucin (465) and laureoxanyne (473) (Scheme 21). 498 These results demonstrated that BrPO is the enzyme that catalyzes the direct bromo-ether cyclization of (3E,6R,7R)-laurediol to deacetyllaurencin, and this was the first direct experimental evidence for the possible biosynthetic pathway leading to the laurencin skeleton. 498 These results also revealed that the geometry of the enyne unit in the substrate (3E-or 3Z-laurediol) plays an important role in the production of acetogenins with 7,13-epoxy (e.g., laurefucin 465) or 6,12-epoxy (e.g., prelaureatin 485) framework (Scheme 21).…”
Section: Biosynthesis Of C 15 -Acetogeninsmentioning
confidence: 85%
See 1 more Smart Citation
“…Further reaction of deacetyllaurencin with BrPO yielded bicyclic ACGs such as laurefucin (465) and laureoxanyne (473) (Scheme 21). 498 These results demonstrated that BrPO is the enzyme that catalyzes the direct bromo-ether cyclization of (3E,6R,7R)-laurediol to deacetyllaurencin, and this was the first direct experimental evidence for the possible biosynthetic pathway leading to the laurencin skeleton. 498 These results also revealed that the geometry of the enyne unit in the substrate (3E-or 3Z-laurediol) plays an important role in the production of acetogenins with 7,13-epoxy (e.g., laurefucin 465) or 6,12-epoxy (e.g., prelaureatin 485) framework (Scheme 21).…”
Section: Biosynthesis Of C 15 -Acetogeninsmentioning
confidence: 85%
“…495,496 In 1992, the same group described a single-step, LPO-catalyzed intramolecular cyclization of (3Z,6S,7S)-laurediol to produce laureatin (481) and its key intermediate prelaureatin (485). 497 The result also suggests that laurediols are the precursors of Laurencia derived ACGs, and that LPO has very low substrate specificity.…”
Section: Biosynthesis Of C 15 -Acetogeninsmentioning
confidence: 99%
“…Fukuzawa and coworkers reported the enzymatic formation of medium-sized cyclic bromo-ethers found in Laurencia using lactoperoxidase (LPO) (Fukuzawa et al, 1990;Ishihara et al, 1997) or BPO (Fukuzawa et al, 1994), the latter of which was partially purified from Laurencia nipponica. They proposed without any proof that the bromine atom(s) in the brominated compounds derived from marine organisms could be introduced via bromo cationic species that is generated by the two-electron oxidation of bromide ion with BPO and hydrogen peroxide.…”
Section: Brominated Acetogenins and Terpenoids Which Have Been Isolamentioning
confidence: 99%
“…Additional halogenated metabolites with a novel chemical structure still continue to be discovered from this unique genus (Blunt et al, 2008). However, studies of the biosynthesis of halogenated metabolites from Laurencia are rare, except for the enzymatic formation of 5 medium-sized cyclic bromo-ethers using lactoperoxidase (LPO) (Fukuzawa et al, 1990;Ishihara et al, 1997) or bromoperoxidase (BPO) that was partially purified from Laurencia nipponica Yamada (Fukuzawa et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation